Systematic Review: Factors Influencing HIV Status Self-Disclosure Among MSM And Non-MSM Groups - Saktia, Bunga Harumi; Novirsa, Randy; Masrizal, Masrizal (UNIVERSITAS ALIFAH PADANG, 2026)
Background: HIV status self-disclosure is a critical determinant of transmission prevention, treatment adherence, and psychosocial wellbeing among people living with HIV/AIDS (PLWHA). Despite its public health significance, disclosure rates remain suboptimal across diverse populations, particularly among men who have sex with men (MSM) and non-MSM groups.Objective: This systematic review aimed to identify and synthesize factors influencing HIV status self-disclosure among PLWHA, with a specific focus on comparative differences between MSM and non-MSM populations.Methods: A systematic search was conducted across PubMed, Scopus, Science Direct, and Google Scholar, covering publications from January 2020 to December 2024. Study selection followed PRISMA 2020 guidelines using a predefined PICO framework. Two independent reviewers screened studies, and methodological quality was assessed using the Newcastle-Ottawa Scale (NOS). Data were synthesized narratively across three thematic domains.Results: From 1,125 initial records, 10 studies met the inclusion criteria (6 cross-sectional, 4 case-control). Three thematic domains were identified: psychological factors (stigma, HIV knowledge, self-acceptance), social factors (partner communication, social support, relationship quality), and structural factors (ART duration, residential setting, healthcare confidentiality). MSM faced distinctive barriers through dual stigmatization related to HIV status and sexual orientation, whereas non-MSM populations were more strongly influenced by gender-based power dynamics, economic dependency, and community-level stigma.Conclusion: HIV disclosure is a multifactorial process requiring differentiated, multi-level interventions targeting stigma reduction, social support strengthening, and improved healthcare confidentiality across both population groups.